Making A Moral Choice In Arthur Miller's The Death Of A Salesman Drama (1949): An Existentialist Approach - Pratiwi, Meylanie, Drs. Muhammad Thoyibi, M. S., Siti Fatimah, S,Pd. M. Hum (2013)
The major issue of this study is how to make a moral choice for searching meaningful of life reflected in Arthur Miller's The Death of a Salesman Drama. The objective of the study is to analyze the drama based on the structural elements and also to analyze the drama based on the existentialist approach. This study belongs to descriptive qualitative research. There are two types of data source. Namely primary and secondary data source. The primary data is the drama itself. Meanwhile the secondary data sources are the other materials related to the study. Both of the data are collected through library research and analyzed by descriptive analyzed. Based on the analysis the researcher draws the following conclusions. First, based on the structural analysis of each elements, it show that the character and characterization, setting, plot, style and theme are connected each other. They are unity that makes a good quality of drama. Second, based on the existentialist analysis, there is an existentialist value in the drama. Arthur Miller illustrated an existentialist phenomenon in which an individual is making the right way in his life. Although this is the difficult choice in his life, he is willing to take the risk and also be responsible for his choices.